Self-assembled angiopep-2 modified lipid-poly (hypoxic radiosensitized polyprodrug) nanoparticles delivery TMZ for glioma synergistic TMZ and RT therapy - Zhenkun Zong; Lei Hua; Zhen Wang; Haoyue Xu; Chengkun Ye; Bomin Pan; Zongren Zhao; Longzhen Zhang; Jun Lu; Hongmei Liu; Rutong Yu (Taylor & Francis Group, 2019)
The addition of temozolomide (TMZ) to radiotherapy (RT) improves survival of patients with glioblastoma (GBM). However, TMZ + RT causes excess toxicity in patients. In this study, we prepared angiopep-2 (A2) modified lipid-poly (hypoxic radiosensitized polyprodrug) nanoparticles for TMZ delivery (A2-P(MIs)25/TMZ) to achieve synergistic effects against glioma. This A2-P(MIs)25/TMZ display highly promising advantages: (1) a hydrophobic P-(MIs)25 core where poorly water-soluble TMZ can be encapsulated; (2) nitro groups of the hydrophobic P-(MIs)25 core that are converted into hydrophilic amino groups (P(NH2s)25) under low oxygen conditions to mimic the oxygen-increased sensitization to RT; (3) a lipid monolayer at the interface of the core and the shell to modify the A2 (a specific ligand for low-density lipoprotein receptor-related protein-1 (LRP-1), which are expressed in the blood-brain barrier (BBB) and human glioma cells), thereby enhancing the drug encapsulation efficiency in glioma. These nanoparticles appear as a promising and robust nanoplatforms for TMZ and hypoxic cell radiosensitization delivery.